Household bargaining and the design of couples' income taxation - Kerstin Roeder; Helmuth Cremer; Jean-Marie Lozachmeur; Dario Maldonado (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
The paper studies the design of couples income taxation when consumption and labor supply decisions within the couple are made in a cooperative way according to some bargaining scheme. Specifically, the couple maximizes a weighted sum of the spouses utilities. In the first part of the paper, the spouses bargaining weights (specific to each couple) are exogenously given. In the second part, these bargaining weights are endogenous, and depend on the spouses respective contributions to total family income. The information structure is the traditional one in Mirrleesian nonlinear income tax models. However, while the household s total consumption is publicly observable, the consumption levels of the individual spouses are not observable. The social welfare function is utilitarian. We show that the expression for a spouses marginal income tax rate includes a Pigouvian (paternalistic) and an incentive term. With exogenous weights the Pigouvian term favors a marginal subsidy (tax) for the high-weight (lowweight) spouse, whose labor supply otherwise tends to be too low (high). In some cases both terms have the same sign and imply a positive marginal tax for the low-weight spouse and a negative one for the high-weight spouse.
Keywords: H21; H31; D10; 330